Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Lipase enzyme immobilization on synthetic beaded macroporous copolymers for kinetic resolution of chiral drugs intermediates - Bhushan, Indu; Parshad, Rajinder; Qazi, Gulam Nabi; Ingavle, Ganesh C.; Rajan, C. R.; Ponrathnam, Surendera; Gupta, Vijay Kumar (Process Biochemistry, 2008)
Lipase isolated from Arthrobacter sp. (bacterial strain, MTCC No. 5125) at RRL Jammu, being used for various process development. Arthrobacter sp. lipase (ABL) now has been immobilized on synthetic polymers and reused many a times. In this investigation number of various synthetic macroporous alkylated glycidyl epoxy copolymers with varying hydrophobicity, pore volume and surface area were prepared and used for this study. Among all the polymers prepared and used only two epoxy polymers GMA-EGDM 75-20(I) and GMA-EGDM 75-30(I) with particle size in the range of 150-450 nm, epoxy groups 80 and 70%, tertiary amino groups 20 and 30% was found suitable for immobilization of lipase (ABL). Dibutyl amine (DBA) incorporation created an internal pore radii 20-50 nm and hydrophobic microenvironment in both the polymers for binding the enzyme, which led to improvement in stability and enatioselectivity in racemic resolution process especially by binding to one of the isomers. The optimal ABL binding capacity of polymer GMA-EGDM 75-20(I) was 60 units, 34 mg protein and GMA-EGDM 75-30(l) was 36 units, 21 mg protein/g polymer. The immobilized lipase matrices displayed enhanced pH, thermal, organic solvent and long-term storage stability. Both the immobilized enzyme matrices were tested firstly for the hydrolysis of triglycerides using tributyrin as substrate. After testing, both the matrices were reused for racemic resolution of ethyl-3-hydroxy-3-phenyl propanoate (fluoxetine intermediate, an antidepressant drug) and racemic chiral auxiliary, acetyl-1-phenyl ethanol (intermediate of many chiral drugs) for 15 cycles. These immobilized lipase matrices have shown very high stability on recycling, high-enantioselectivity, high conversion and faster recovery of product compare to free enzyme, therefore these matrices may find use in kinetic resolution process developments. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-phenyl ethanol and enantioselectivity; chiral resolution; enantiomeric excess (ee); ethyl-3-hydroxy-3-phenyl propanoate; Immobilization; Lipase